IPCC's current conceptualization of 'vulnerability' needs more clarification for climate change vulnerability assessments. (1st February 2022) - Ishtiaque, Asif; Estoque, Ronald C; Eakin, Hallie; Parajuli, Jagadish; Rabby, Yasin Wahid
Abstract: In this Short Communication, we raise the concern that the existing conceptualization of 'vulnerability', introduced in the IPCC Fifth Assessment Report (AR5), is not facilitative for standalone vulnerability assessments and that this conceptualization has not been well accepted by the vulnerability researchers. We identify three key reasons for low adoption of the AR5 conceptualization in climate change vulnerability assessments, and urge the IPCC Working Group II to clarify how the current conceptualization of 'vulnerability' can facilitate standalone climate change vulnerability assessments. We propose treating 'exposure' not only as a precondition for vulnerability but also as a secondary driver of vulnerability to capture the influence of differential exposure. Highlights: IPCC's current conceptualization of 'vulnerability' is not facilitative for standalone vulnerability assessments. This conceptualization has not been well accepted by the vulnerability researchers. We identified three key reasons for the low adoption of the AR5 conceptualization in climate change vulnerability assessments. We argue that 'exposure' should be treated as both precondition and secondary driver of vulnerability.